2009
DOI: 10.1097/rlu.0b013e3181becfe0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of F-18 FDOPA, F-18 FDG, and F-18 FLT-PET/CT for Metabolic Imaging of Low Grade Gliomas

Abstract: F-18 FDOPA scan is superior to both F-18 FLT and F-18 FDG for visualization of primary and recurrent low grade gliomas. F-18-FLT should not be considered for evaluation of recurrent low grade gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 10 publications
1
60
0
3
Order By: Relevance
“…When compared with 18 F-FDG, presently the most widely available PET tracer, amino-acid analogs have shown higher sensitivity to gliomas because of the higher tumor-to-normal-tissue background ratios (9). Among amino-acid PET tracers, 18 F-3,4-dihydroxyphenylalanine ( 18 F-DOPA) is largely unexplored in pediatric brain tumors, with only 3 children evaluated in prior studies (10,11), and no data are available specifically regarding IAs. In this prospective study, we evaluated the diagnostic role, clinical contribution, and prognostic value of fused 18 F-DOPA PET/MR images in a selected population of pediatric patients with supratentorial IAs.…”
mentioning
confidence: 99%
“…When compared with 18 F-FDG, presently the most widely available PET tracer, amino-acid analogs have shown higher sensitivity to gliomas because of the higher tumor-to-normal-tissue background ratios (9). Among amino-acid PET tracers, 18 F-3,4-dihydroxyphenylalanine ( 18 F-DOPA) is largely unexplored in pediatric brain tumors, with only 3 children evaluated in prior studies (10,11), and no data are available specifically regarding IAs. In this prospective study, we evaluated the diagnostic role, clinical contribution, and prognostic value of fused 18 F-DOPA PET/MR images in a selected population of pediatric patients with supratentorial IAs.…”
mentioning
confidence: 99%
“…3 In the present case (a grade II astrocytoma), though the FDG uptake was very high (SUVmax, 15.0) but FLT showed definite abnormal uptake and identified the exact distribution of the recurrent lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the utility of F-18 FLT in predicting the grade of gliomas. [3][4][5][6][7][8] Yamamoto et al in their study demonstrated significant correlation between metabolic volumes of recurrent glioblastoma multiforme and the volumes defined on MRI. 9 FLT was also better than methionine in tumor grading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FDOPA-PET has clinical utility in brain tumor imaging [24,25]. A study comparing FDOPA and FDG for the detection of primary and recurrent brain tumors in 30 patients showed that FDOPA had a sensitivity of 96%, as opposed to 61% for FDG [26].…”
Section: Synthetic Amino Acidsmentioning
confidence: 99%